The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4081/jlimnol.2021.2019
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist and bibliography of the Diaptomidae (Copepoda, Calanoida) of Italy, Corsica, and the Maltese islands

Abstract: Calanoids of the family Diaptomidae are the most widespread copepods in the lentic inland waters of the Palearctic region. In Italy, studies on the family date back to the end of 19th century. Since then, several papers contributed to increasing the knowledge on their presence, distribution, and ecological preferences. Nevertheless, new records for the area and the discovery of putative new species stress that the current knowledge on these inland water crustaceans is still far from being exhaustive. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 112 publications
(277 reference statements)
0
9
1
Order By: Relevance
“…A species occurring at high altitudes in southern areas is thus expected to occur at lower altitudes in northern areas, as routinely observed for other diaptomid species (e.g. Hemidiaptomus gurneyi (Roy, 1927), which is strictly linked to mountainous area in Sicily but a typical lowland species in Peninsular Italy, see Alfonso et al, 2021), whereas the opposite pattern is clearly observed in D. cyaneus. Second, the occurrence of D. cyaneus in permanent, sometimes even fish-inhabited, water bodies has never been observed in the southernmost regions of the study area (i.e.…”
Section: Diaptomid Copepodsmentioning
confidence: 67%
See 3 more Smart Citations
“…A species occurring at high altitudes in southern areas is thus expected to occur at lower altitudes in northern areas, as routinely observed for other diaptomid species (e.g. Hemidiaptomus gurneyi (Roy, 1927), which is strictly linked to mountainous area in Sicily but a typical lowland species in Peninsular Italy, see Alfonso et al, 2021), whereas the opposite pattern is clearly observed in D. cyaneus. Second, the occurrence of D. cyaneus in permanent, sometimes even fish-inhabited, water bodies has never been observed in the southernmost regions of the study area (i.e.…”
Section: Diaptomid Copepodsmentioning
confidence: 67%
“…Second, the occurrence of D. cyaneus in permanent, sometimes even fish-inhabited, water bodies has never been observed in the southernmost regions of the study area (i.e. Tunisia, Sicily, Apulia and Sardinia), whereas the only populations occurring in northern Italy and Corsica are occurring in such a habitat (Alfonso et al, 2021).…”
Section: Diaptomid Copepodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Identification of collected copepods was performed based on Dussart [48,49], Kiefer [50], Einsle [51,52], Karaytug [53], Hoły ńska et al [54], Hoły ńska [55], Alekseev and Defaye [56], and Miracle et al [57]. Copepod nomenclature here follows Ruffo and Stoch [58], with the exceptions of the genera Arctodiaptomus Kiefer, 1932, and Acanthocyclops Kiefer, 1927, for which we follow Alfonso et al [59] and Miracle et al [57], respectively. Notwithstanding the doubts raised by some authors (e.g., [60,61]), we here consider D. bicuspidatus (Claus, 1857) and D. lubbocki (Brady, 1869) as different taxa of species level.…”
Section: Codementioning
confidence: 99%